Synovial Tissue Sampling in Rheumatological Practice—Past Developments and Future Perspectives - Humby, Frances C. (Frontiers in Medicine, 2019)
Synovial biopsies are performed in routine clinical care in order to refine diagnosis as well as within a research setting. Progress in the development of minimally invasive synovial sampling methods in the last century has accelerated and facilitated novel insights into disease pathogenesis. This review discusses the development of synovial biopsy techniques as well as examining the three currently most commonly used approaches: arthroscopic, blind needle biopsy and ultrasound guided approaches. It also highlights major research advances driven through synovial research and considers future developments.